Evaluation of alignment error of micropore X-ray optics caused by hot plastic deformation. (18th May 2018) - Numazawa, Masaki; Ishi, Daiki; Ezoe, Yuichiro; Takeuchi, Kazuma; Terada, Masaru; Fujitani, Maiko; Ishikawa, Kumi; Nakajima, Kazuo; Morishita, Kohei; Ohashi, Takaya; Mitsuda, Kazuhisa; Nakamura, Kasumi; et al.
Abstract: We report on the evaluation and characterization of micro-electromechanical system (MEMS) X-ray optics produced by silicon dry etching and hot plastic deformation. Sidewalls of micropores formed by etching through a silicon wafer are used as X-ray reflecting mirrors. The wafer is deformed into a spherical shape to focus parallel incidence X-rays. We quantitatively evaluated a mirror alignment error using an X-ray pencil beam (Al Kα line at 1.49 keV). The deviation angle caused only by the deformation was estimated from angular shifts of the X-ray focusing point before and after the deformation to be 2.7 ± 0.3 arcmin on average within the optics. This gives an angular resolution of 12.9 ± 1.4 arcmin in half-power diameter (HPD). The surface profile of the deformed optics measured using a NH-3Ns surface profiler (Mitaka Kohki) also indicated that the resolution was 11.4 ± 0.9 arcmin in HPD, suggesting that we can simply evaluate the alignment error caused by the hot plastic deformation.